Diosgenin relieves oxaliplatin-induced pain by affecting TLR4/NF-κB inflammatory signaling and the gut microbiota. Issue 1 (15th December 2022) - Man, Shuli; Xie, Lu; Liu, Xuanshuo; Wang, Genbei; Liu, Changxiao; Gao, Wenyuan
Abstract : Diosgenin extracted from fenugreek, yam and other foods exhibits a wide range of pharmacological activities, especially for the treatment of pain and other nervous system diseases. Abstract : Diosgenin extracted from fenugreek, yam and other foods exhibits a wide range of pharmacological activities, especially for the treatment of pain and other nervous system diseases. However, its role in oxaliplatin-induced peripheral neuropathy (OIPN) is unclear. To explore its detailed mechanism on the pain caused by chemotherapy, we carried out this experiment. In this study, the effects of diosgenin on injured PC12 cells and OIPN mice were examined. The results showed that diosgenin not only protected PC12 from injury, but also reduced the mechanical withdrawal threshold and cold hyperalgesia in OIPN mice. Diosgenin inhibited oxidative stress, the cell glial fibrillary acidic protein, and the pro-inflammatory cytokines such as tumor necrosis factor-α, toll-like receptor 4 and nuclear factor-κB in the brain. Furthermore, the fecal microbiota transplantation experiment indicated that diosgenin improved OIPN through regulation of the gut microbiota. All in all, diosgenin ameliorates peripheral neuropathy and is worthy of further study in the treatment of neuropathic pain.